Performance of multiple combined profile cold-formed steel column - Septiropa, Zamzami (2021)
In the construction of low-rise buildings, cold-formed steel (CFS) as column is rarely used even though it is an important component. Previous studies have shown that the main weakness of CFS is its buckling behaviour due to the thin nature of CFS section. By combining multiple similar profiles to form a new profile using selfdrilling screw connectors, strong column can be obtained in terms of the crosssectional capacity and buckling resistance. This research investigates the performance of multiple combined profile columns, to obtain the relevant limits for the capacity design factor of multiple combined profile sections. To achieve this research aim, theoretical analysis and experimental works were carried out based on C7575 CChannel profile. Firstly, the testing of the material properties of the C7575 was conducted, to be followed by the analysis and testing of single profile member capacity with variations in length of 300, 500, 1000, 1750 and 2500 mm. Then, analysis of the combined profiles that comprises of double-back-to-back (dBB), double-lips-to-lips (dLL) and double-flange-to-flange (dFF) profiles were performed to obtain the new cross-sectional capacity. To obtain the ideal spacing of self-drilling screw connector, a compressive test was performed on the combined dFF and combined dBB profiles with variations in spacing of 25, 50, 75, 100 and 125 mm using 300 mm length sample. The combined dFF and dBB profiles were assembled and arranged to form several multiple combination profiles, namely 2dFF, 4dFF, 6dFF, and 8dFF to obtain the adequate strength and performance for low-rise building column applications. It is found that C7575 profile possess the ultimate strength, fu = 616.27 N/mm2 , yield strength, fy = 597.93 N/mm2 , modulus of elasticity, E = 209 GPa and shear modulus, G = 80.38 GPa. It also found that, double-back-to-back (dBB) and double-flange toflange (dFF) are the ideal configurations for multiple combined profiles of CFS. The patterns yielded an increase in the cross-sectional capacity with a ratio ranging from 1.7 to 1.8. As for the spacing of screws, the ideal distance for dBB is 75 mm to 125 mm while for dFF, it is 75 mm to 100 mm. Observations on the performance of the eight-double-flange-to-flange (8dFF) multiple combined profile shows that the profile did not experience any rotation deformation. In general, the recommended value of imperfection factor, a for the C-channel profile type is 0.34 while for other types of profile CFS, the value of a can be taken as 0.76. The a value of 0.76 even though it produces a match between the results of theoretical and experimental calculations, it is too confident for a calculation. Based on the theoretical formulation, it is found that a new value of a for 8dFF multiple combined profile is equal to 1.14. This new value of a is therefore proposed, to determine the appropriate reduction factors for buckling about y axis, %y and z axis, %z for the type of 8dFF multiple combined profile. The research concluded that 8dFF multiple combined profile can be used efficiently as column for low-rise building structure.